METODE BROMCRESOL GREEN (BCG) DAN BROMCRESOL PURPLE (BCP) PADA SIROSIS HATI YANG MENDAPAT INFUS ALBUMIN - Miftahul Ilmiah; Leonita Anniwati; Soehartini Soehartini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Albumin infusion is one of the therapeutic options in hypoalbuminemia patients. Serum albumin can be used to determine the albumininfusion therapy, prognosis and monitoring of liver cirrhosis. The time difference in measurement of serum albumin by bromcresol green(BCG) and bromcresol purple (BCP) methods can give different results. Serum albumin examination was done in 20 sera taken fromcirrhosis patients. Serum albumin was then evaluated before treatment, one (1) hour and 24 hours after the patient received an infusionof albumin and examined by bromcresol green (BCG) and bromcresol purple (BCP) methods. The serum albumin level by BCG methodincreased with a coefficient of 0.12 (p-value=0.022) with BCG method before (1.94±0.32 mg/dL) and after one (1) hour (2.06±0.32mg/dL) receiving intravenous albumin. The coefficient of albumin levels before and after 24 hours (2.12±0.38 mg/dL) was 0.18 (pvalue=0.07), whereas the increased levels of serum albumin after one (1) hour and after 24 hours of intravenous albumin, were notsignificant (p-value=0.467). The BCP method showed that serum albumin before, after one (1) hour and after 24 hours receivingintravenous albumin were 1.68±0.36 mg/dL, 1.87±0.36 mg/dL and 2.12±0.63 mg/dL respectively. The albumin levels showed asignificant increase before and after one (1) hour infusion of albumin (p-value=0.00), both levels shown before and after 24 hours(p-value=0.001), as well as one (1) hour and 24 hours after receiving intravenous albumin (p-value=0.04). The results of this studyshowed that increased serum albumin by BCG method could be detected after 1 (one) hour, whereas by BCP method could only be detectedafter 24 hours receiving intravenous albumin.